2020
DOI: 10.7717/peerj.8524
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal domain of rhamnosyltransferase EpsF influences exopolysaccharide chain length determination in Streptococcus thermophilus 05-34

Abstract: Glycosyltransferases are key enzymes involved in the assembly of repeating units of exopolysaccharides (EPS). A glycosyltransferase generally consists of the N-terminal and the C-terminal domain, however, the functional role of these domains in EPS biosynthesis remains largely unknown. In this study, homologous overexpression was employed to investigate the effects of EpsFN, a truncated form of rhamnosyltransferase EpsF with only the N-terminal domain, on EPS biosynthesis in Streptococcus thermophilus 05-34. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
6
1
Order By: Relevance
“…We also observed that epsF overexpression increased EPS yields by 17%. This observation was inconsistent with Wang et al (2020), who indicated that epsF overexpression did not affect EPS production in S. thermophilus. This may have been due to strain-specific differences.…”
Section: Identification Of Key Genes In the Eps Biosynthetic Pathway ...contrasting
confidence: 69%
“…We also observed that epsF overexpression increased EPS yields by 17%. This observation was inconsistent with Wang et al (2020), who indicated that epsF overexpression did not affect EPS production in S. thermophilus. This may have been due to strain-specific differences.…”
Section: Identification Of Key Genes In the Eps Biosynthetic Pathway ...contrasting
confidence: 69%
“…S. thermophilus 05CK and 05epsCh 6 were grown under static conditions at 37°C in MRS broth supplemented with 5 μg/mL chloramphenicol for 30 h prior to protein extraction. Protein extraction and Western blot were performed as previously described ( Wang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The HPGPC system consisted of Agilent 1260 series HPLC system (Agilent, United States) and Shodex SUGAR KS series containing KS-804 and KS-805 columns (Shodex Co., Tokyo, Japan). The purified EPS was detected using refractive index detector (RI-2000, Waters, United States) according to the method which we used previously ( Wang et al, 2020 ). Briefly, 40 μg purified EPS was eluted with 20 mM NaCl at a flow rate of 0.8 mL/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene products of epsCD , which are proposed to form a membrane-located complex, also bear topological and sequence similarities to ABC transport systems, suggesting that they play a dual role in EPS transport and chain length control (Stingele et al 1996 ). It is assumed that the transcription level of epsC (and likely epsD) influences chain length, while the availability of nucleotide sugars may also modulate chain length also (Wang et al 2020 ). Polymerization of the EPS repeating subunits is suggested to be a function of EpsJ, possibly through complexation with EpsC and EpsD (Stingele et al 1996 ).…”
Section: Eps Produced By S Thermophilusmentioning
confidence: 99%